Decreasing In Freshwater Production Due To Vacuum Pressure Decreasing On Multi Effect Distillation Installation - Hery Sonawan; Muhamad Deary; Auliansyah Afrianthoni (Mestro, 2021)
A case study in a steam power plant has been conducted and reported. There was a case of decrease in the freshwater production rate in multi effect distillation installations that may disrupt the operation of the power plant. The cause was suspected by the drop in vacuum pressure in the evaporation chamber. The study was conducted by studying the MED installation process diagram and performing the theoretical calculations of energy and mass equilibrium in each chamber. To make it easier to find the properties of water in the energy calculation then add ins water_97 in Microsoft Excel is added.Calculations were undertaken in two modes, commissioning period and 2016 operation mode. The difference of the two modes was vacuum pressure level in each chamber. Vacuum pressure level in 2016 operation mode was lower than commissioning mode. The calculation at commissioning mode resulted in a production rate of 133.56 ton/h, while the actual condition at that time was 127 ton/h. Calculations in 2016 operation mode produced a theoretical fresh water production rate of 101.37 ton/h.